DETERMINAN PERBEDAAN NILAI PERUSAHAAN PUBLIK DI INDONESIA, THAILAND, DAN SINGAPURA DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL PEMODERASI - Puspita Romadhona; Nurmala Ahmar; Darmansyah Darmansyah (JURNAL LENTERA AKUNTANSI, 2018)
AbstractThis study examines the differences determinant in firm value of public companies in Indonesia, Thailand, and Singapore, institutional ownership as a moderator. The sampling technique used is purposive sampling with criteria public listed company, issuing financial statements that entered into the top index for five years. Sample used is 130 observation in Indonesia, 175 observation in Thailand, and 135 observation in Singapore with SEM-PLS analysis method using WarpPLS 6.0 and multigrup analysis. The results indicate that profitability has significant effect to firm value either in Indonesia, Thailand, or in Singapore. Solvability has no significant effect to firm value in Indonesia, but in Thailand solvability has negative effect on firm value and in Singapore solvability has positive effect to firm value. Ownership institutional able to moderate the effect of profitability and solvability on the value of firms in Singapore, while in Thailand institutional ownership can’t moderate profitability effect, but moderate solvability of firm value. While in Indonesia, institutional ownership unable to moderate the effect of profitability and solvability on firm value. The result of multigrup analysis shows there is a difference determinant of firm value with institutional ownership as moderator between Indonesia with Thailand, Indonesia with Singapore, and Thailand with Singapore.Keywords: Profitability, Solvability, Institutional Ownership, Total Assets, Price To Book Value.